PERRMOHONAN IZIN PERKAWINAN POLIGAMI DI PENGADILAN AGAMA SUMBER DALAM PERSPEKTIF FIQH DAN UNDANG-UNDANG PERKAWINAN NOMOR 1 TAHUN 1974 - superadmin superadmin (IAIC (Institut Agama Islam Cirebon), 2020)
ABSTRACT Polygamy is a marriage bond for a man with more than one wife at the same time, but is limited to four people. According to the Marriage Act before committing polygamy must first obtain permission from the Religious Court and apply for permission for polygamy in the local Religious Court.The research problem consists of: How does the application process permits polygamy in the Religious Sumber? Why polygamous marriage license application in court Sumber? and How to permit polygamous marriage in the perspective of religious law and marriage law No. 1 of 1974? in writing this thesis using qualitative methods and presented descriptively.Implementation of the application for permit polygamy Sumber Religious Court in accordance with the Marriage Law, Article 4, paragraph 1, which states that a husband who will have more than one wife, then it must apply for permission for polygamy in the local religious court. The application letter should contain evidence and full reasons underlying the application for a license is polygamous, and must meet the requirements stipulated by applicable legislation. Religious Court judge will grant the petition polygamy if the reasons and sayart-requisite to apply for permission for polygamy are met.Under the provisions of formal permission for polygamy in the Religious Court explicitly not found and included in the Qur'an and the Sunnah of the Prophet Muhammad but implicitly can be found from the source and the arguments of the law by doing ijtihad, interpretation, and Islamic legal thought as Istislah (look for the benefit) and sadd adh-dhari'ah (occlude kemudharatan).In socio-formal judicial philosophy of the provisions relating to mandatory religion court permission for polygamy is that the existence and consequences of polygamous marriages run in accordance with what is desired religious Shari'ah, namely the creation of households that can revive the values of justice on the basis mawadah and rahmah in order mu'asyarah bil ma'ruf, realization tranquil family life so as to reap the expected happiness by each spouse.